Shadow Epitaxy for In Situ Growth of Generic Semiconductor/Superconductor Hybrids. Issue 23 (26th April 2020) - Carrad, Damon J.; Bjergfelt, Martin; Kanne, Thomas; Aagesen, Martin; Krizek, Filip; Fiordaliso, Elisabetta M.; Johnson, Erik; Nygård, Jesper; Jespersen, Thomas Sand
Abstract: Uniform, defect‐free crystal interfaces and surfaces are crucial ingredients for realizing high‐performance nanoscale devices. A pertinent example is that advances in gate‐tunable and topological superconductivity using semiconductor/superconductor electronic devices are currently built on the hard proximity‐induced superconducting gap obtained from epitaxial indium arsenide/aluminum heterostructures. Fabrication of devices requires selective etch processes; these exist only for InAs/Al hybrids, precluding the use of other, potentially superior material combinations. This work introduces a crystal growth platform—based on 3D structuring of growth substrates—which enables synthesis of semiconductor nanowire hybrids with in situ patterned superconductor shells. The platform eliminates the need for etching, thereby enabling full freedom in the choice of hybrid constituents. All of the most frequently used superconducting hybrid device architectures are realized and characterized. These devices exhibit increased yield and electrostatic stability compared to etched devices, and evidence of ballistic superconductivity is observed. In addition to aluminum, hybrid structures based on tantalum, niobium, and vanadium are presented. Abstract : A novel growth platform, "shadow epitaxy, " is presented, enabling growth of patterned superconductor/metal layers on semiconductor nanostructures, with generic choice of materials and a wide range of electronic device geometries. Using the platform, new hybrid materials for topological superconductivity research are evaluated, with resultant devices exhibiting high yield and electrostatic stability due to obviation of post‐process damage.